2007
DOI: 10.1002/ejlt.200700105
|View full text |Cite
|
Sign up to set email alerts
|

Seeds and oil of the Styrian oil pumpkin: Components and biological activities

Abstract: Cucurbita pepo subsp. pepo var. Styriaca is a phylogenetically young member of the Cucurbita spp. since the mutation leading to dark green seeds with stunted outer hulls arose only in the 19th century. This mutation defined the so‐called Styrian oil pumpkin and facilitated the production of Styrian pumpkin seed oil. It is a regional specialty oil in the south‐eastern part of Europe. In this article, we describe the production and economic value of this edible oil as well as its composition on a molecular basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 71 publications
7
96
3
6
Order By: Relevance
“…The presence of high amounts of linoleic acid also suggested that the analyzed PSOs could be used as a good source of essential fatty acids. High oleic acid contents, detected in all the analyzed oil samples, is also favorable from a cardio-protective and nutritional viewpoint (Fruhwirth et al, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…The presence of high amounts of linoleic acid also suggested that the analyzed PSOs could be used as a good source of essential fatty acids. High oleic acid contents, detected in all the analyzed oil samples, is also favorable from a cardio-protective and nutritional viewpoint (Fruhwirth et al, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…The daily intake of phenolic antioxidants has played an important role in reducing the risk of developing diseases, such as atherosclerosis, cardiovascular diseases, cancer, infections and Alzheimer's disease. They also present antimicrobial and antiviral action (Fruhwirth and Hermetter 2007) but, depending on the amount ingested, they can cause undesirable effects, such as inhibition of certain digestive enzymes, e. g. trypsin, forming complexes with proteins and decreasing their digestibility (Sathe 2002). In the literature, there is no consensus on the recommended intake of phenolic compounds; therefore, consumption levels considered acceptable were not found (Sathe, 2002;Peuckert et al, 2010;Marques et al, 2013).…”
Section: Institute Of Medicine Of the Natural Academies 2005a)mentioning
confidence: 99%
“…The medicinal features of the pumpkin (Cucurbita pepo L., Cucurbitaceae family) including anti-diabetic, antihypertensive, anti-tumour, immunomodulatory, antibacterial, intestinal anti-parasitic, and anti-inflammatory activities have been described in several studies (Caili et al, 2006;Fruhwirth and Hermetter, 2007;Danilcenko et al, 2011). Notably, pumpkin seeds are rich in proteins and biologically active substances, including essential and nonessential amino acids, tocopherols, carotenoids (especially β-carotene and lutein), mineral elements, fibre, and other compounds considered to exhibit valuable dietetic and medicinal properties (Caili et al, 2006;Glew et al, 2006;Nakic et al, 2006;Fruhwirth and Hermetter, 2007;Stevenson et al, 2007;Kreft et al, 2009;Badr et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, pumpkin seeds are rich in proteins and biologically active substances, including essential and nonessential amino acids, tocopherols, carotenoids (especially β-carotene and lutein), mineral elements, fibre, and other compounds considered to exhibit valuable dietetic and medicinal properties (Caili et al, 2006;Glew et al, 2006;Nakic et al, 2006;Fruhwirth and Hermetter, 2007;Stevenson et al, 2007;Kreft et al, 2009;Badr et al, 2011).…”
Section: Introductionmentioning
confidence: 99%